2018
DOI: 10.3126/janr.v1i1.22219
|View full text |Cite
|
Sign up to set email alerts
|

Economics of fish production at Chitwan district, Nepal

Abstract: A study was conducted in 2016 to analyze the economics of fish production at Chitwan District of Nepal. Three study sites: East, West and South part of Chitwan were selected purposively. A total of 90 households, 30 from each study site were selected randomly and were interviewed by using pre-tested semi structured questionnaire. Secondary data needed for the study were obtained from DADO, MOAD, NARC and other related organizations working on fisheries and aquaculture sector. Descriptive statistics and extende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 1 publication
6
10
0
1
Order By: Relevance
“…The enterprise lies in the second stage of production. This finding is in consistent with that of Sharma et al (2018) where decreasing return to scale was obtained and with Timothy and John (2011) in their study on analysis of profitability of fish farming among women in Osun State, Nigeria.…”
Section: Returns To Scale/ Elasticity Of Productionsupporting
confidence: 91%
See 1 more Smart Citation
“…The enterprise lies in the second stage of production. This finding is in consistent with that of Sharma et al (2018) where decreasing return to scale was obtained and with Timothy and John (2011) in their study on analysis of profitability of fish farming among women in Osun State, Nigeria.…”
Section: Returns To Scale/ Elasticity Of Productionsupporting
confidence: 91%
“…664448.99/ha which accounted for 68.36% of the total cost. Similar findings were obtained by Sharma et al, (2018) where feed cost contributed 28% and labour cost contributed 25% to the total cost incurred during production process. Yemi and Okiemute (2008) also obtained similar findings where variable cost accounted for 72.95% and fixed cost accounted for 27.05% of the total cost.…”
Section: Cost Of Productionsupporting
confidence: 85%
“…For this ,scale value of 1,0.8,0.6,0.4 and High cost of feed shows most serious problem as its index value is 0.94 so it rank 'I' among all 0.2 was used to most serious, serious, moderate, a little bit and least serious problem respectively. The problem index value was found quite similar with the data obtained by Geetu and Misgana (2015) and Sharma et al (2018) [6,11].…”
Section: Ranking Of Production Problemssupporting
confidence: 88%
“…For example Janssen (2017) found that Benefit-Cost Ratio for aquaculture production is 1.42. Sharma et al (2018) found the benefit-cost ratio as 1.63 for fish farming in Nepal. They also reported feed cost as the largest cost item with 35.5% contribution to total variable cost of production.…”
Section: Methodsmentioning
confidence: 99%